Bibliometric analysis of trends in dental management of the children with Autism Spectrum Disorder (ASD) - Kanwalpreet Kaur; Ravinder S. Saini; Syed Altafuddin Quadri; Gustavo Vicentis Oliveira Fernandes; Anna Avetisyan; Seyed Ali Mosaddad; Artak Heboyan (Discover Mental Health)
Abstract This study aimed to present a complete overview of the trends, difficulties, and improvements in dental treatment for children diagnosed with autism spectrum disorder through rigorous bibliometric analysis. The dimensional database field was chosen to enable the inclusion and recall of the greatest number of relevant entries. All peer-reviewed international journals published between 2004 and 2023 were included in this study. The sophisticated search keywords' Autistic Disorder" OR "Autism Spectrum Disorder" AND "Dental management" were used. Studies that examined patterns and difficulties in the dental care of children with ASD were included in the inclusion and exclusion criteria for this analysis. Among the listed countries, The United States had the highest number of documents and citations. Barbara Sheller is the most cited author, followed closely by Arthur H.Friedlander, Michael E.Mahler, and John A.Yagiela. This study also revealed that most articles involved multinational collaborations, highlighting the global scope of dental research. The United States leads in terms of research output and citations, followed by India and China. Research on autism spectrum disorder has grown substantially over the past few years, and the authors recommend that future research concentrate on creating effective behavioral techniques that will assist children with autism spectrum disorder in coping with dental treatment.